Extramedullary relapse of acute lymphoblastic leukemia in breast: A rare presentation - Thanka J; Krishnarathinam K; Rajendiran S (Wolters Kluwer Medknow Publications, 2010)
Unusual sites of relapses following allogenic hematopoietic stem cell transplantation (HSCT) for acute lymphoblastic leukemia (ALL) are rarely reported. Our report describes a thirty-two-year old female, who developed extramedullary (EM) breast relapse after allogenic HSCT for pre B cell Philadelphia chromosome negative ALL. She had no evidence of leukemia in her marrow demonstrating 100% full donor chimerism, while she had ALL relapse in her breast.